Digital pathology in the diagnostic setting: beyond technology into best practice and service management. Issue 5 (6th January 2017) - Cheng, Chee Leong; Tan, Puay Hoon
Abstract : Digital pathology (DP) and whole-slide imaging (WSI) technology have matured substantially over the last few years and there is growing evidence from validation studies that WSI is comparable to glass slides for histopathology diagnosis, although with some limitations, which can be appropriately minimised. Whether the controlled environment of validation studies translates to the same level of robustness when WSI is used in the actual diagnostic setting depends on the technical quality of WSI acquisition and on factors that influence the pre-image acquisition variables including the quality of glass slide inputs, and postimage acquisition variables such as access and use of WSI. The concept of 'DP service management' is introduced to fulfil the holistic needs of a laboratory intending to use the DP solution incorporating WSI for diagnostic purposes. The DP service management team should be an integral part of the diagnostic laboratory as it plays a central role undertaking responsibility to address an extensive range of issues from technical and training to governance and accreditation, hence ensuring a viable and sustainable diagnostic DP integration and usage. The pathologist as a specialist in the field and key decision maker of histopathology diagnoses has the duty and responsibility to acquaint and familiarise with DP and WSI when using the technology, especially on their indications and limitations, so as to take full advantage of these tools to enhance diagnostic quality.